Clinical Values and Markers of Radiation-Induced Liver Disease for Hepatocellular Carcinoma With Portal Vein Tumor Thrombus Treated With Stereotactic Body Radiotherapy - Jia, Jun; Sun, Jing; Duan, Xuezhang; Li, Wengang (Frontiers in Oncology, 2021)
Background: Information about radiation-induced liver disease (RILD) in hepatocellular carcinoma (HCC) patients preexisting hepatitis B cirrhosis with portal vein tumor thrombus (PVTT) extended to the main portal vein treated with stereotactic body radiotherapy (SBRT) is still inadequate and the predictive markers for RILD have not been cleared in these patients. The aim of the study is to identify factors that can be used to predict RILD and to evaluate the influence of RILD in these patients. Methods: In our study, 59 patients were analyzed and evaluated from December 2015 to June 2019, according to the entry criteria. After treatment, 59 patients were followed up within the first month and then every 3 months. Hematology test, tumor markers, three-phasic CT scan of lung, and CT or MRI scan of liver were underwent at each recheck. Results: Median overall survival time was 10.7 months (range, 5.8 to 14.9). RILD appeared in 17 of the 59 patients (28.8%) at the 3rd month after SBRT. In the univariate analysis, not only the CP score class (A or B) but also each different pretreatment CP score (p < 0.05) was significant predictive factor of RILD. More RILD cases were detected with the increase of CP score. The recovery rate decreased as baseline CP score increased (p < 0.05). It was found that the overall survival time was affected by only baseline CP score and RILD (p < 0.05). Conclusions: The development of RILD has a dependency on the CP score in these patients. CP score before treatment and RILD are significantly associated with the overall survival. SBRT is an effective and safe method for patients with CP ≤ B7. For patients with CP-B8, liver function should be monitored more frequently. It is not safe enough for the SBRT treatment in CP-B9 patients.